Characterization of Plasmodium phosphatidylserine decarboxylase expressed in yeast and application for inhibitor screening - Choi, Jae-Yeon (Mol Microbiol, 2015)
Phospholipid biosynthesis is critical for the development, differentiation and pathogenesis of several eukaryotic pathogens. Genetic studies have validated the pathway for phosphatidylethanolamine synthesis from phosphatidylserine catalyzed by phosphatidylserine decarboxylase enzymes (PSD) as a suitable target for development of antimicrobials; however no inhibitors of this class of enzymes have been discovered. We show that the Plasmodium falciparum PSD can restore the essential function of the yeast gene in strains requiring PSD for growth. Genetic, biochemical and metabolic analyses demonstrate that amino acids between positions 40 and 70 of the parasite enzyme are critical for proenzyme processing and decarboxylase activity. We used the essential role of Plasmodium PSD in yeast as a tool for screening a library of anti-malarials. One of these compounds is 7-chloro-N-(4-ethoxyphenyl)-4-quinolinamine, an inhibitor with potent activity against P. falciparum, and low toxicity toward mammalian cells. We synthesized an analog of this compound and showed that it inhibits PfPSD activity and eliminates Plasmodium yoelii infection in mice. These results highlight the importance of 4-quinolinamines as a novel class of drugs targeting membrane biogenesis via inhibition of PSD activity